2022
DOI: 10.3390/app12126009
|View full text |Cite
|
Sign up to set email alerts
|

Research on Intelligent Detection Algorithm of the Single Anchored Mooring Area for Maritime Autonomous Surface Ships

Abstract: Mooring area detection represents one of the key technological problems that must be solved in the development of Maritime Autonomous Surface Ships (MASS). In view of the lack of research on the current detection methods for ship mooring area, a new intelligent detection algorithm of the single anchored mooring area for MASS was proposed in this study, aiming at improving the detection ability and accuracy of the MASS mooring area. Firstly, the laws of short period swinging motion, long period circumferential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A previous study, ref. [45], showed that under Beaufort 7 wind conditions, when considering factors like ship length, water depth, and anchoring chain length, the radius is smaller than the radius derived from calculations involving the rule-based methods determined by Equation (8). Therefore, using the rule-based radius, as evident from the more conservative results presented in this paper, is considered a reasonable approach.…”
Section: Modeling Characteristic Regions Of the Port Of Ulsanmentioning
confidence: 67%
“…A previous study, ref. [45], showed that under Beaufort 7 wind conditions, when considering factors like ship length, water depth, and anchoring chain length, the radius is smaller than the radius derived from calculations involving the rule-based methods determined by Equation (8). Therefore, using the rule-based radius, as evident from the more conservative results presented in this paper, is considered a reasonable approach.…”
Section: Modeling Characteristic Regions Of the Port Of Ulsanmentioning
confidence: 67%